2014
DOI: 10.1090/s1056-3911-2014-00637-8
|View full text |Cite
|
Sign up to set email alerts
|

Bridgeland stability conditions on threefolds II: An application to Fujita’s conjecture

Abstract: ABSTRACT. We construct new t-structures on the derived category of coherent sheaves on smooth projective threefolds. We conjecture that they give Bridgeland stability conditions near the large volume limit. We show that this conjecture is equivalent to a BogomolovGieseker type inequality for the third Chern character of certain stable complexes. We also conjecture a stronger inequality, and prove it in the case of projective space, and for various examples.Finally, we prove a version of the classical Bogomolov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 24 publications
1
52
0
Order By: Relevance
“…If L[i] ∈ B α,β holds for a line bundle L and i ∈ {0, 1}, then L[i] is tilt-stable (see [5,Proposition 7.4.1]). By Lemma 4.3, we get immediately O(−1) [3], O [1], O(1) ∈ A α,β , A α,β [1] .…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…If L[i] ∈ B α,β holds for a line bundle L and i ∈ {0, 1}, then L[i] is tilt-stable (see [5,Proposition 7.4.1]). By Lemma 4.3, we get immediately O(−1) [3], O [1], O(1) ∈ A α,β , A α,β [1] .…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, C is isomorphic to the category of finitely generated modules over some finite dimensional algebra A and O(−1) [3], S(−1) [2], O [1], O(1) are the simple objects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It depends on the choice of two divisor classes ω, B ∈ NS(X ) R with ω ample. It was shown that this conjecture would imply the existence of Bridgeland stability conditions, 2 and, in the companion paper [6], a version of an open case of Fujita's conjecture, on the very ampleness of adjoint line bundles on threefolds.…”
Section: Stability Conditions On Threefolds Via a Conjectural Bogomolmentioning
confidence: 97%
“…Until recent work by Maciocia and Piyaratne [29,30], they were only known to exist on threefolds whose derived category admits a full exceptional collection. Possible applications of stability conditions range from modularity properties of generating functions of Donaldson-Thomas invariants [43,45] to Reider-type theorems for adjoint linear series [6].…”
Section: Stability Conditions On Threefolds Via a Conjectural Bogomolmentioning
confidence: 99%